2006
DOI: 10.1080/02770900600878990
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ventilation, Breathlessness Perception and Alexithymia in Near-Fatal Asthma

Abstract: Several studies have demonstrated impaired control of ventilation in some patients with near-fatal asthma (NFA). The objective of our study was to determine a possible relationship between alexithymia (a cognitive processing disorder), control of ventilation, and breathlessness perception in patients who had an NFA attack. We analyzed data from 100 subjects: 50 with NFA, 25 asthmatics without NFA, and 25 non-asthmatic controls. Ventilatory responses to hypoxia and hypercapnia were measured by the rebreathing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
4
21
0
2
Order By: Relevance
“…As regards alexithymia, our results agree only partially with data previously obtained by Plaza [16] and Serrano [17], who found that alexithymia was more prevalent in NFA patients than in non-NFA patients. These authors considered the TAS total score but did not examine each factor separately.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As regards alexithymia, our results agree only partially with data previously obtained by Plaza [16] and Serrano [17], who found that alexithymia was more prevalent in NFA patients than in non-NFA patients. These authors considered the TAS total score but did not examine each factor separately.…”
Section: Discussionsupporting
confidence: 75%
“…Some studies did not find differences between NFA patients and non-NFA patients in depression or anxiety [10][11][12], knowledge about illness management [13,14], or adherence to pharmacological treatment [13,15], whereas other investigations showed a higher prevalence of anxiety [8] and alexithymia [16,17], and lower levels of medication adherence [18] in NFA patients. Different factors could be involved in these discrepant results.…”
mentioning
confidence: 99%
“…In agreement with our findings, a recent study found "difficulty identifying feelings" to be strongly associated with HRQOL in a group of patients with pain secondary to neuromuscular disease [35], and to be also the component of alexithymia accounting for the somatization scores in a group of subjects sustaining cerebral trauma [14]. "Difficulty identifying feelings" have also been proven to be related to an increased number of non-scheduled visits to the emergency department [15], more severe relapses and an increased frequency of hospitalizations in asthma patients [10,36]. The proposed mechanism through which "difficulty identifying feelings" causes this effect is by an increased number of somatic complaints [37].…”
Section: Discussionmentioning
confidence: 96%
“…Psychosocial factors may be associated with poorly controlled and potentially fatal asthma. 36,37,46,68,69 Patients with a poor perception of dyspnea have been identified in some 62,64,79 but not all 27,36,63 studies of risk factors for potentially fatal asthma, but there is no simple, validated way to test for this factor in a primary care setting. 101 Failure of the treating physician to appreciate the severity of the acute asthma attack and to initiate appropriately aggressive therapy has also been shown to be a risk factor for a fatal outcome.…”
Section: The Case Continuedmentioning
confidence: 99%